2005
DOI: 10.1111/j.1745-4514.2005.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Bacillus Subtilis Jm-3 Protease From Anchovy Sauce

Abstract: Bacillus subtilis JM‐3 was isolated from anchovy sauce naturally fermented in an underground cellar at 15 ± 3C for 3 years. The activity of the B. subtilis protease was highest in the 40–60% ammonium sulfate fraction. The yield of the purified protease was 5.3%, and its purification ratio was 35.6 folds. The molecular weight of the B. subtilis protease was 17.1 kDa, and its Km and Vmaxvalues were 1.75 μg/mL and 318 μM 1/min, respectively. The optimal temperature for protease activity was 60C, but optimal stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…11). As per previous results regarding protease purification, the values of specific activities observed for different microbial species such as B. licheniformis, B. subtilis, and B. megaterium were 13.33-159381 U/mg of protein with 4.25-200 purification fold [28,29]. …”
Section: Partial Purification Of Enzyme By Ammonium Sulfate Purificationmentioning
confidence: 85%
See 1 more Smart Citation
“…11). As per previous results regarding protease purification, the values of specific activities observed for different microbial species such as B. licheniformis, B. subtilis, and B. megaterium were 13.33-159381 U/mg of protein with 4.25-200 purification fold [28,29]. …”
Section: Partial Purification Of Enzyme By Ammonium Sulfate Purificationmentioning
confidence: 85%
“…Wide-ranging results of protease purification (4.25-200-fold) with various specific activities (13.34 U/mg of protein) and % recovery (2-21%) have been described for different microbial species such as Bacillus licheniformis, Bacillus subtilis, and Bacillus megaterium (Fig. 10) [28][29][30].…”
Section: Partial Purification Of Enzyme By Ammonium Sulfate Purificationmentioning
confidence: 99%
“…were characterized by Murao et al (1988) and Toogood et al (1995). Kim (2002) characterized the acid protease produced by B. subtilis JM-3, and reported that optimal pH and temperature were 5.5 and 60 o C, respectively. The high values of biomass on the level 33.8 mg/ml were observed in large range of temperature and pH (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Kim and S.M. Kim, 2005;Fu et al, 2008;Chung, 1984;Hwang et al, 2010). The specific activity of the R. japonicus protease II was the highest among these five proteases, and that of the B. megaterium KLP-98 was the lowest.…”
Section: Enzyme Activitymentioning
confidence: 99%
“…However, the protease produced by B. Kim, 2005;Fu et al, 2008). Thus, these proteases were salt-tolerant proteases which can be used in soybean paste and soy sauce productions.…”
Section: Effects Of Nacl Concentration On Enzyme Activitymentioning
confidence: 99%